The presence of antiautonomic membrane receptor antibodies do not correlate with brain lesions in Chagas' disease A presença de anticorpos anti-autonômicos não se correlaciona a lesões cerebrais na doença de Chagas - Marco O. Py; Leonardo Maciel; Roberto C. Pedrosa; Jose H. M. Nascimento; Emiliano Medei (Arquivos de Neuro-Psiquiatria)
We previously demonstrated correlation between parasympathetic dysfunction and brain white matter lesions in chronic chagasic patients. OBJECTIVE: To correlate serum functional circulating antibodies with beta adrenergic (Ab-β), muscarinic (Ab-M) or muscarinic and beta adrenergic (Ab-Mβ) activity, the autonomic system function and brain lesions in chronic chagasic patients. METHOD: In fifteen consecutive chagasic patients, the autonomic nervous system was evaluated and brain magnetic resonance imaging (MRI) was performed. The sera of all patients were tested to the presence of circulating functional antibodies. RESULTS: Sera from 11 of 15 chronic chagasic patients had some activity (Ab-β: 7; Ab-M: 1; Ab-Mβ: 3); however, there was no significant correlation between the presence of antibodies and the autonomic system function or the presence of hyperintensities in MRI. CONCLUSION: The mechanism involved in the genesis of hyperintense lesions seen in brain MRI of chronic chagasic patients is still unresolved, although apparently related to parasympathetic dysfunction. A correlação entre disfunção parassimpática e lesões de substância branca cerebral em pacientes chagásicos já foi previamente demonstrada. OBJETIVO: Correlacionar a presença de anticorpos circulantes funcionais com atividade beta-adrenérgica (Ab-β), muscarínica (Ab-M) ou muscarínica e beta adrenérgica (Ab-Mβ), a presença de disautonomia e lesões de substância branca cerebral em pacientes chagásicos crônicos. MÉTODO: Em quinze pacientes chagásicos consecutivos, foram realizados a avaliação do sistema nervoso autônomo e ressonância magnética (RM) do crânio. O soro dos pacientes foi testado para a presença de anticorpos funcionais circulantes. RESULTADOS: O soro de 11 dos 15 pacientes chagásicos apresentou alguma atividade (Ab-β: 7; Ab-M: 1; Ab-Mβ: 3); porém não houve correlação significativa entre a presença de anticorpos circulantes e disautonomia ou de hiperintensidades à RM. CONCLUSÃO: O mecanismo envolvido na gênese das lesões hiperintensas à RM do crânio dos pacientes chagásicos crônicos não está esclarecida ainda, apesar de aparentemente relacionada à disfunção parassimpática.